Cerebral Abscess by Fonsecaea monophora—The First Case Reported in Germany. (4th June 2018) - Helbig, Sina; Thuermer, Alexander; Dengl, Markus; Krukowski, Pawel; de With, Katja
Abstract: We report the first case of cerebral Fonsecaea monophora infection in a German woman without immunodeficiency or travel history. F. monophora infection is a rare differential diagnosis of cerebral tumors; it was previously considered a tropical fungus. This case adds to the scarce reports in nontropical regions.